Emergency Department length of stay and disposal of patients in Chitwan medical college, Nepal - Lamsal, Daya Ram; Raut, Krishna Bahadur; Adhikari, Parash (Journal of Chitwan Medical College, 2019)
Background: Measuring patients Length of Stay (LOS) in the emergency Department (ED) is one of the assessments of quality indicators in terms of clinical, managerial and public satisfaction prospective. Waiting time standard is defined and its impact is analyzed in many hospitals especially in developed countries. Policy of emergency operations to reduce length of stay helps to manage overcrowding, spares time to treat critical patient and minimize preventable death. The study was done to assess length of stay and disposal of patients visiting emergency department in Chitwan Medical College. Methods: This was a retrospective study conducted from 01/10/2018 to 30/09/2019 at Chitwan Medical college, Nepal. Patients electronic records were retrieved from medical record section of all patients visiting to emergency department. Ethical approval was obtained from ethical review committee. Results: Medial Length of Stay (LOS) was 3.84 hours (Interquartile range 0.4 hours to 84 hours) 54.54% discharged, 40.83% admitted from ED. Conclusion: Median Length of Stay (LOS) in the Emergency Department (ED) was 3.84 hours which is satisfactory as compared to similar studies. Majority of patients discharged after treatment from ED.